EVALUASI STRATEGI KEBIJAKAN DALAM MENINGKATKAN AKSES DAN KUALITAS PENDIDIKAN MADRASAH DI INDONESIA. - Fahruddin; Titi Kadi (STKIP Subang, 2026)
This research aims to conduct an in-depth evaluation of the policy strategies implemented by the Ministry of Religion of the Republic of Indonesia in improving the accessibility and quality of madrasah education. The main problems identified include quality disparities between regions, limitations of digital infrastructure in disadvantaged, frontier, and outermost (3T) areas, and structural obstacles due to the dualism of the national education system that causes madrasas to often be considered second-class educational institutions. The importance of this research lies in the need for strategic recommendations to support the vision of a Golden Indonesia 2045 through the strengthening of intellectually and spiritually superior human resources. The methodology used is a qualitative approach with literature study methods and document analysis on the latest regulations, including the Ministry of Religion's Strategic Plan 2025-2029 and the Madrasah Education Quality Reform (MEQR) program. The results of the study show that the implementation of the e-RKAM system, the Indonesian Madrasah Competency Assessment (AKMI), and affirmative policies in the Admission of New Students (PPDB) have significantly increased governance transparency and expanded access for marginalized groups. However, the effectiveness of the policy is still constrained by the low digital literacy of educators and the inequality of technological support facilities. These findings underscore the importance of multi-sector collaboration and locally-context-based policy personalization to ensure the sustainability of the quality of Islamic education in Indonesia.